An Ultrafast and Highly Stable Potassium–Organic Battery. Issue 51 (26th October 2018) - Fan, Ling; Ma, Ruifang; Wang, Jue; Yang, Hongguan; Lu, Bingan
Abstract: Potassium–organic batteries have a great potential for applications in the grid‐scale energy storage owing to their low cost and abundant resources, although they suffer from the inferior cycle stability, fast capacity decay, and low power density. A highly reversible phase transformation of the organic cathode during potassiation/depotassiation is the key factor for the capacity retention, as revealed here. Consequently, the potassium–organic battery achieves a high power density of 9796 W kg −1, a remarkable energy efficiency of 89%, a long cycle stability for 1000 cycles, a superior areal capacity around 2 mA h cm −2, and a long‐term cycling time over 8 months. Besides, the full cells also exhibit a superior rate performance and good cycle stability over 3000 cycles. This work provides new insight into the stabilization of the organic cathode, and demonstrates the enormous potential of organic cathodes for application in high‐power potassium‐ion batteries (PIBs), which may bring PIBs to new heights. Abstract : A potassium–organic battery achieves a high power density of 9796 W kg −1, a remarkable energy efficiency of 89%, a long cycle stability for 1000 cycles, and a superior areal capacity around 2 mA h cm −2 and a long‐term cycling time over 8 months.